2011
DOI: 10.1136/annrheumdis-2011-200038
|View full text |Cite
|
Sign up to set email alerts
|

In early rheumatoid arthritis, patients with a good initial response to methotrexate have excellent 2-year clinical outcomes, but radiological progression is not fully prevented: data from the methotrexate responders population in the SWEFOT trial

Abstract: Most early RA patients who achieve low disease activity after 3-4 months of methotrexate monotherapy continue to have low disease activity during 2 years follow-up, and additional treatment is needed infrequently. Some radiological progression occurs in most patients, and may be marked or severe in some, even despite sustained DAS28 remission. Close monitoring for radiological progression is thus warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 33 publications
3
51
0
3
Order By: Relevance
“…We have previously shown that smoking, functional impairment, and female sex strongly predict a nonresponse to MTX at 3 months of follow‐up 13, whereas those who responded well to MTX did well during 2 years of follow‐up under standard care 23. All clinical guidelines recommend that treatment start with MTX, while there are several options to choose from in cases of nonresponse: cDMARD combinations and different biologic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that smoking, functional impairment, and female sex strongly predict a nonresponse to MTX at 3 months of follow‐up 13, whereas those who responded well to MTX did well during 2 years of follow‐up under standard care 23. All clinical guidelines recommend that treatment start with MTX, while there are several options to choose from in cases of nonresponse: cDMARD combinations and different biologic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Комбинированная терапия МТ и ГИБП эффектив-нее монотерапии МТ, однако более чем у 1/3 пациентов на фоне монотерапии МТ наблюдается стойкое выраженное улучшение клинических проявлений РА и они не нужда-ются в интенсификации терапии [123,291]. При этом эф-фективность монотерапии МТ можно существенно повы-сить путем проведения короткого курса ГК в низких дозах, по крайней мере при раннем РА [292,293].…”
Section: Discussionunclassified
“…Early initiation of treatment in RA assists patients in attaining improved outcomes and drug-free remission by profoundly modifying the pathogenesis of RA. [31][32][33][34] RA patients on early DMARDs show a significantly lower disease progression rate, irrespective of the differences in treatment regimen or disease characteristics. [35][36][37] Studies have also shown that early intervention group had significantly lower radiographic damage at 5 years.…”
Section: Discussionmentioning
confidence: 99%